TDDB modeling depending on interfacial conditions in magnetic tunnel junctions. (6th September 2017) - Choi, Chul-Min; Sukegawa, Hiroaki; Mitani, Seiji; Song, Yun-Heub
Abstract: We investigated time-dependent dielectric breakdown (TDDB) modeling for MgO dielectrics with/without Mg insertion of MgO-based magnetic tunnel junctions (MTJs). The number of permanent trap sites at the no-Mg insertion interface was much larger than that at the Mg-inserted interface as determined by interval voltage stress (IVS) tests. The interfacial conditions related to trap sites at MgO dielectrics give rise to the different TDDB modeling. Here, we confirmed that the TDDB curves obtained from the constant voltage stress (CVS) tests for the Mg inserted interface case were well fitted by the power-law voltage V model, while the case of no-Mg inserted interface showed a good correlation to the 1/E model. The difference in the TDDB models related to interfacial conditions was understood based on theoretical and experimental results. Finally, we concluded that it is necessary to select an appropriate reliability model depending upon the presence or absence of the trap sites at dielectric interfaces.